God of justice and mercy a theological commentary on Judges - Hamley, Isabelle M. (London SCM Press, 2021)
Judges is one of the most misunderstood and underused books in the Old Testament - it is a text people outside of the higher echelons of Old Testament academia are afraid of. Too often it is dismissed as too violent, outrageous, or simply too puzzling for practical use - or full of tales which are only of any use as children's stories or as simple moralising tales for adults. Focusing on core theological themes across the book, this commentary is predicated on the idea that far from being too awkward to touch, Judges in fact holds up a mirror to today's world, with its stories of abuses of power, war and violence, and the human tendency towards individualism. Overall, the commentary argues that in Judges we are given the story of a people who keep getting life and faith increasingly wrong, and the story of God's response to their cry for justice and mercy. Bridging the gap between accessibility and scholarly rigour, this commentary offers an excellent tool for ordinands, students, teachers in higher education and preachers to engage with the theology of the book in its Old Testament context as well as how its message is revealed in the New Testament and continues to speak today
Introduction -- Setting the scene (1.1-3.6) -- Othniel and Ehud (3.7-5.31) -- Gideon (6-8) -- Abimelech (9) -- Jephthah and the Minor Judges (10-12) -- Samson (13-16) -- Micah and the Danites (17-18) -- Dismemberment (19-21.24) -- The refrain (21.25).
Includes bibliographical references (pages 282-288) and indexes
Keywords: Bible -- Commentaries; Bible; Commentaries